Implikasi Normalisasi Hubungan Diplomatik Negara-Negara Timur Tengah dengan Israel terhadap Prospek Kemerdekaan Palestina: Telaah Konstruktivisme - Minhajuddin, Minhajuddin; Umam, Ahmad Khoirul (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2023)
This research examines the process of normalizing diplomatic ties between middle eastern countries with Israel and its implications for the Palestine independence. The author uses constructivism paradigm in analyzing the aims of middle eastern countries towards Israel’s existence and the struggle of the Palestine. The political decision of the Middle Eastern countries in normalizing relations with Israel is viewed as an anomaly while Israel continues to occupy Palestine territory. It can be observed that there are economic and military assistance from United States and Israel to Middle Eastern countries. If it is elaborated, the diplomatic normalization isn’t about it but a shared value. Middle Eastern countries, United States, and Israel have a deal that the threat in the Middle East region comes from Iran, which is becoming increasingly dominant. The constructivism explain the concept of threat has transformed originally from Israel and the United States to a threat from Iran.